Penerapan Media Pembelajaran Budaya Sekolah Islami Berbasis Multimedia - Wahyuni, Wahyuni; Iqbal, Muhammad; Rizani, Fitri; Najmuddin, Najmuddin (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2023)
Islamic education is a process of directing human development (ri'ayah) in terms of body, mind, language, behavior and social and religious life directed towards goodness towards perfection, with the existence of Islamic education in the world of education will train students' feelings in such a way that in their life attitudes actions, decisions and approaches to all types of knowledge are influenced by Islamic ethical values. Multimedia allows computer users to get output in a much richer form than conventional table and graph media. Multimedia-based learning media is a tool or intermediary that is useful to facilitate the teaching and learning process, in order to streamline communication between teachers and students. This is very helpful for teachers in teaching and makes it easier for students to receive and understand lessons. This process requires teachers who are able to harmonize between learning media and multimedia-based learning methods.